Utilization of Blood Meal, Slaughterhouse Waste and Bio Gas Slurry into Fertilizer - Ginting, Nurzainah (Indonesian Journal of Agricultural Research, 2020)
In slaughterhouses the burden of waste such as excessive blood volume causesÂ  waste process with sewage treatment pond cannot work optimally. Blood should be separated and processed into other products such as blood meal. This study aims to prove that addition of blood meal produces good quality organic fertilizer. In this research, the fermentor used in the composting process was biogas slurry. The study used CRD (Complete Randomized Design) with 4 treatments: without blood meal; blood meal 6.5%; blood meal 13% and blood meal 19.5%. There was no difference between the treatments at fertilizer temperature, pH and C/N except treatment 19.5% blood meal on C/N. Application of blood meal by 19.5% in the fourth week on C/N was 12.17 as a requirement for mature fertilizer. The treatment by adding 375 g blood meal on 6 kg livestock feces and 6 kg feed leftover while use biogas slurry as the fermentor was a novel organic fertilizer formula.